Validation of the Online Learning Readiness Self-Check survey. Issue 4 (2nd October 2021) - Cheon, Jongpil; Cheng, Jiaming; Cho, Moon-Heum
ABSTRACT: This study reports the development and validation of the Online Learning Readiness Self-Check (OLRSC), a self-report survey designed to examine nontraditional students' readiness for online learning. A total of 505 prospective online learners with diverse background participated in the study. Data from 252 randomly selected participants were used to conduct the exploratory factor analysis, which extracted six factors of online learning readiness. Data from the remaining 253 participants were used for the confirmatory factor analysis, which supported the six-factor structure of the OLRSC with a reduction of 39 to 23 items. This instrument about online learning readiness can be used for prospective online learners to identify their strength and weakness. The diagnostic information can also be used to provide meaningful guides or aids to future nontraditional students.